Rhodium(III)-Catalyzed C–H Activation Mediated Synthesis of Isoquinolones from Amides and Cyclopropenes - Hyster, Todd K.; Rovis, Tomislav (Synlett, 2013)
We have developed a synthesis of 4-substituted isoquinolones from the rhodium(III)-catalyzed, C–H activation mediated coupling of O-pivaloyl benzhydroxamic acids and 3,3-disubstituted cyclopropenes. Experiments suggest the formation of a [4.1.0] bicyclic system, which can open under acidic conditions to generate the desired isoquinolone.
Keywords: C–H activation; heterocycles; isoquinolone; cyclopropene; donor–acceptor cyclopropane